2011
DOI: 10.1309/ajcpar39bfwnhwro
|View full text |Cite
|
Sign up to set email alerts
|

T-Regulatory Cells in Lymph Nodes

Abstract: Because T-regulatory cells (Tregs) can harmfully impair HIV-specific responses or beneficially limit immune activation, we compared the number of Tregs in lymph nodes from 48 HIV+ patients and 106 HIV- subjects. By using a microscope counting grid, we found that the mean ± SD number of Tregs in lymph nodes was 3 times greater in HIV+ males than HIV+ females (23.5 ± 20.7 vs 7.8 ± 7.7; P = .0006) and almost twice as great in HIV+ males than HIV- males (23.5 ± 20.7 vs 13.5 ± 15.5; P = .04). There were fewer Tregs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(28 reference statements)
1
0
0
Order By: Relevance
“…The numbers of CD3 + cells expressing Foxp3 in the B-cell follicles was significantly reduced in acute infection (p=0.0022, n=7) and contracted even further in chronic infection (p<0.0001, n=8), when compared to naïve (n=8) animals (Figure 3G and Supplemental Figure 3B). The number of Foxp3 + CD3 + cells in the T-zone did not change, as described by others (Figure 3H) (52). …”
Section: Resultssupporting
confidence: 84%
“…The numbers of CD3 + cells expressing Foxp3 in the B-cell follicles was significantly reduced in acute infection (p=0.0022, n=7) and contracted even further in chronic infection (p<0.0001, n=8), when compared to naïve (n=8) animals (Figure 3G and Supplemental Figure 3B). The number of Foxp3 + CD3 + cells in the T-zone did not change, as described by others (Figure 3H) (52). …”
Section: Resultssupporting
confidence: 84%
“…Methods for the immunohistochemical detection of other immunoregulatory proteinsincluding OX40, LAG-3, and CD137-in FFPE tissue sections have also been optimized, and the regulation of their expression is an area of active investigation (111)(112)(113). Preliminary studies have indicated that there is wide variation in the number of tumor-infiltrating immune cells expressing each of these markers (S. Lovitch & S. Rodig, unpublished data), and it remains to be determined whether their detection and number within tumor-biopsy specimens are predictive of the clinical response to therapies targeting these molecules.…”
Section: Detecting Immune Checkpoint Proteinsmentioning
confidence: 99%